I Really Know You: How Influencers Can Increase Audience Engagement by Referencing Their Close Social Ties - Chung, Jaeyeon (Jae); Ding, Yu; Kalra, Ajay (Journal of Consumer Research, 2023)
Despite firms’ continued interest in using influencers to reach their target consumers, academic and practical insights are limited on what levers an influencer can use to enhance audience engagement using their posts. We demonstrate that posting stories with or about people whom they share close ties with—such as family, friends, and romantic partners—can be one effective lever. Content that incorporates close social ties can be effective for several reasons: it may increase perceptions of authenticity, enhance perceived similarity, increase the perception that the influencer possesses more warmth, and could satisfy viewers’ interpersonal curiosity. We analyze texts and photographs of 55,631 posts of 763 influencers on Instagram, and after controlling for several variables, we find robust support that consumers “like” posts that reference close social ties. Furthermore, this effect enhances when first-person pronouns are used to describe special moments with these close ties. We supplement the Instagram data with an experimental approach and confirm the relationship between close ties and consumer engagement. Managerially, this is a useful insight as we also show that sponsored posts tend to be perceived negatively compared to non-sponsored posts; yet, embedding social ties on the sponsored posts can mitigate consumers’ negative responses.